Features of Metabolism in Chronic Wound Remodelling - Pavlov, Sergey; Babenko, Nataliia; Kumetchko, Marina; Litvinova, Olga; Mikhaylusov, Rostyslav (Scripta Medica, 2024)
Background/Aim: The treatment of chronic wounds continues to be a pressing problem throughout the world. Healing occurs through some evolutionarily conserved biochemical pathways. The mechanisms of development of disorders of reparative regeneration are not fully understood. The work aimed to study the dynamics of changes in metabolic parameters during the healing of chronic wounds. Methods: Healthy Wistar rats were divided into two groups. The animals of the first group were intact. Chronic wounds were simulated for the animals of the second group. On days 7, 14 and 28 after wound creation, the animals were euthanised. Biochemical parameters such as glucose, total protein, albumin, cholesterol, urea, creatinine, aspartate aminotransferase (AST), alanine aminotransferase (ALT) and alkaline phosphatase (ALP) were assessed in the blood serum of animals.Results: It was found that the maximum decrease in glucose and total protein levels in the blood serum of animals in the experimental groups compared to intact animals was observed 2 weeks after surgery: the glucose concentration in rats was 1.7 times lower (p < 0.001). The level of albumin in the blood serum of experimental animals compared to intact animals was reduced by 1.5 times after 14 days (p < 0.001) and by 1.2 times after 28 days (p < 0.01). A week after surgery, the concentration of urea in the blood serum of experimental animals was 1.3 times higher (p < 0.01) than in intact rats and by day 28 after surgery, the urea level was 1.4 times higher (p < 0.001). The reduction in cholesterol and creatinine levels was not significant. An increase in AST, AST and ALP levels in the blood serum of experimental animals was shown. An increase in the blood serum of animals 7 days after surgery compared to the indicators of intact animals: ALP concentrations by 2.8 times (p < 0.001) and ALT concentrations by 1.4 times (p < 0.001) was established. The AST level significantly increased 14 days after surgery (p < 0.05). Conclusions: The study of metabolic parameters allows monitoring of the state of the body during the healing process of wounds to correct treatment tactics.
Keywords: Wound healing; Metabolism; Rats